Analisis Kecemasan Matematika Peserta Didik dalam Menyelesaikan Soal Hots - Rahma Ashari Firmansyah; Danti Lisnawati; Dara Syifa Cahyasari; Dwinda Annisa; Dinda Eka Aprilia (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Emotional factors, particularly math anxiety, significantly influence students’ abilities to solve Higher Order Thinking Skills (HOTS) problems in mathematics learning. This study aims to examine the extent to which math anxiety affects students’ performance and to identify the main challenges experienced when completing HOTS-based assessments. This research employed a qualitative approach with descriptive methods involving 12th-grade high school students categorized into three levels of anxiety: high, moderate, and low. Data were collected through several instruments, including questionnaires, written HOTS tests, interviews, and document analysis. The results reveal variations in students’ abilities to complete HOTS questions based on their anxiety levels. Some students demonstrated the ability to provide accurate solutions, while others experienced difficulties in understanding the core concepts, determining appropriate problem-solving strategies, and analyzing complex mathematical problems. The findings indicate that math anxiety has a significant impact on students’ performance in solving HOTS questions, particularly affecting conceptual understanding, problem-solving accuracy, concentration, and self-confidence. Therefore, addressing emotional factors in mathematics learning is essential to support students in developing higher-order thinking abilities and improving their academic achievement.